2021
DOI: 10.1136/bmjdrc-2020-001416
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of vault RNA 2-1 promoter is a predictor of glycemic response to glucagon-like peptide-1 analog therapy in type 2 diabetes mellitus

Abstract: IntroductionTherapeutic efficiency of glucagon-like peptide-1 (GLP-1) analog is about 50%–70% in type 2 diabetes mellitus (T2DM). Discovery of potential genetic biomarkers for prediction of treatment efficiency of GLP-1 analog before therapy is still necessary. We assess whether DNA methylation was associated with glycemic response to GLP-1 analog therapy in patients with poorly controlled T2DM.Research design and methodsGenomic DNA was extracted from the peripheral blood of training (n=10) and validation (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Also, A allele of a polymorphism in the same gene, that is, rs2346018, correlated with hypomethylation and thus reduced responsiveness to GLP-1 analogs. 88 miRNAs have a role in posttranscriptional regulation of expression. These are 20 to 30 nucleotides-long noncoding RNAs which bind to 3′-UTR of the target primary transcript causing its destabilization and repression of translation.…”
Section: Role Of Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, A allele of a polymorphism in the same gene, that is, rs2346018, correlated with hypomethylation and thus reduced responsiveness to GLP-1 analogs. 88 miRNAs have a role in posttranscriptional regulation of expression. These are 20 to 30 nucleotides-long noncoding RNAs which bind to 3′-UTR of the target primary transcript causing its destabilization and repression of translation.…”
Section: Role Of Epigeneticsmentioning
confidence: 99%
“…Also, A allele of a polymorphism in the same gene, that is, rs2346018, correlated with hypomethylation and thus reduced responsiveness to GLP-1 analogs. 88 …”
Section: Role Of Epigeneticsmentioning
confidence: 99%
“…The methylation status of this epiallele has also been associated with allergies [ 24 ], asthma [ 25 ], infections [ 26 ], and inflammation [ 27 ]. We and others have also shown that both the nc886 methylation status and RNA expression are associated with indicators of glucose metabolism [ 16 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the methylation level or status of nc886 or level of nc886 RNAs transcribed from the locus have been associated with childhood BMI (19), adiposity and cholesterol levels (11), as well as allergies (20), asthma (21), infections (22) and inflammation (23). Interestingly, the nc886 methylation status and the level of nc886 RNAs have also been associated with indicators of glucose metabolism (11,24). These findings suggest that the methylation status of nc886 is a potential molecular mediator of the Developmental Origins of Health and Disease (DOHaD) hypothesis (also known as the Barker hypothesis) (25).…”
Section: Introductionmentioning
confidence: 99%